Analysis of Factors that Influence the Optimization of Risk Management Strategies in Infrastructure Projects - Andy; Indrastuti; Amelia Masza (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
Infrastructure projects frequently face challenges such as cost overruns and schedule delays, which are generally caused by suboptimal risk management practices. This condition highlights the importance of early and integrated planning, sustainable stakeholder collaboration, and evidence-based decision-making. Accordingly, this study aims to identify and analyze the key risk factors that influence the optimization of risk management strategies in infrastructure projects. This study employs a quantitative approach, with data collected through an online questionnaire distributed to 31 infrastructure professionals in Batam City, Indonesia. The respondents consist of project managers, engineers, consultants, and contractors selected using purposive sampling to ensure the relevance of practical experience. Although the sample size is limited, it is considered adequate for an exploratory study focused on the local context. The results indicate that internal risks, particularly inadequate planning and ineffective work management, have a more dominant impact than external risks such as climatic conditions. Other significant factors include financial instability, design changes, and client-driven variations. Statistical analysis using SPSS reveals a significant positive correlation between proactive stakeholder involvement and the effectiveness of risk response strategies. Furthermore, the use of historical data and formal risk documentation contributes to improved mitigation effectiveness. This study concludes that optimizing risk management in infrastructure projects requires an adaptive and evidence-based approach to enhance project resilience and minimize delays and cost overruns.